2011
DOI: 10.1172/jci42917
|View full text |Cite
|
Sign up to set email alerts
|

PUMA-mediated intestinal epithelial apoptosis contributes to ulcerative colitis in humans and mice

Abstract: Intestinal epithelial cell (IEC) apoptosis contributes to the development of ulcerative colitis (UC), an inflammatory bowel disease (IBD) that affects the colon and rectum. Therapies that target the inflammatory cytokine TNF have been found to inhibit IEC apoptosis in patients with IBD, although the mechanism of IEC apoptosis remains unclear. We therefore investigated the role of p53-upregulated modulator of apoptosis (PUMA), a p53 target and proapoptotic BH3-only protein, in colitis and IEC apoptosis, using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
164
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 38 publications
15
164
1
4
Order By: Relevance
“…Intracellular (cytoplasmic and nuclear) PARP1 is known for protection against genomic instability but also controls several forms of cell death, the effect attributed to energetic failure due to NAD ϩ depletion (29), activation of mitochondrial apoptosis inducible factor via its PAR-binding domain (30), or through activation of redoxsensitive cation channel TRPM2 (31) among other mechanisms. Therefore, the protection we observed in Parp1 Ϫ/Ϫ mice from DSS-mediated colitis, a model reliant on a direct toxic and pro-apoptotic effect on colonic epithelial cells (32), could be attributed to the resistance of the colonocytes to DSS-related cytotoxicity. However, the observed lack of protection in B-and T-cell-deficient Parp1 Ϫ/Ϫ mice (Rag2…”
Section: Discussionmentioning
confidence: 88%
“…Intracellular (cytoplasmic and nuclear) PARP1 is known for protection against genomic instability but also controls several forms of cell death, the effect attributed to energetic failure due to NAD ϩ depletion (29), activation of mitochondrial apoptosis inducible factor via its PAR-binding domain (30), or through activation of redoxsensitive cation channel TRPM2 (31) among other mechanisms. Therefore, the protection we observed in Parp1 Ϫ/Ϫ mice from DSS-mediated colitis, a model reliant on a direct toxic and pro-apoptotic effect on colonic epithelial cells (32), could be attributed to the resistance of the colonocytes to DSS-related cytotoxicity. However, the observed lack of protection in B-and T-cell-deficient Parp1 Ϫ/Ϫ mice (Rag2…”
Section: Discussionmentioning
confidence: 88%
“…In HCT116 cells, a human colonic cancer cell line, TNF-α markedly induced PUMA, and the induction was attenuated by 1,25(OH) 2 D 3 ( Figure 9A). PUMA is regulated by NF-κB, and a functional cis-κB site has been identified in the PUMA gene promoter (12,14) (Figure 9B). ChIP assays showed that 1,25(OH) 2 D 3 blocked TNF-α-induced p65 binding to this κB site in HCT116 cells ( Figure 9C), and EMSA confirmed that 1,25(OH) 2 D 3 attenuated TNF-α-induced NF-κB binding to the PUMA κB probe in HCT116 nuclear extracts ( Figure 9D).…”
Section: Reconstitution Of Vdr-null Epithelial Cells With Hvdr Rescuementioning
confidence: 99%
“…Indeed, TNF-α and IFN-γ, two cytokines critical to IBD pathogenesis, induce IEC apoptosis (11). Recent studies demonstrated that p53-upregulated modulator of apoptosis (PUMA) is a key mediator of IEC apoptosis in IBD (12). PUMA is a BH3 domain proapoptotic BCL2 family member that interacts with antiapoptotic BCL2 family members to activate proapoptotic BAX and BAK and trigger mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3, a key enzyme in apoptosis, is activated in apoptotic cells through both extrinsic and intrinsic pathway. This causes colonic destruction with disturbed functions (Qiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%